Inventory of finds and multiphase cemetery by Fort Sokol in Konavle (Archaeologia Adriatica, 2021)
This paper presents the results of the archaeological excavations conducted next to Fort Sokol in Konavle in 2012 and 2013, as well as the results of the anthropological analysis and radiocarbon (14C) dating. The site of Sokol has a long occupation continuity starting from prehistory until the Early Modern Period. The excavation of the area adjoining the fort was divided into four big probes, the one next to its southern side being the most complex. Multiphase cemetery is located along the southern and eastern side of the fort, with a smaller number of graves along its northern side. All probes revealed deep layers formed in earthquakes that were common in the Dubrovnik region. In addition to graves and architecture remains, these layers contained stone boulders that fell off the fort in earthquakes and an abundance of diverse finds dating to a broad time span, from prehistory to the Modern Period. The fort was deserted in 1672. Anthropological analysis encompassed all recovered skeletal remains from preserved grave units regardless of the state of preservation, whereby the remains of 92 individuals were identified, of which 57 adults and 35 children. Analysis of osteological material also documented pathological changes developed antemortem. Radiocarbon (14C) dating was applied on skeletal remains resulting in chronological range from the 5th to the 19th century. The same method was used for dating carbonized almonds that were dated to the Early Iron Age (750 – 400 cal BC).
Keywords: radiocarbon (14C) dating; antiquity; anthropological analysis; archaeological finds; archaeological research; Dunave; Konavle; Modern Period; prehistory; Middle Ages; Fort Sokol; multiphase cemetery